AN EXAMINATION OF THE POWER POLITICS IN THE LEAGUE OF NATIONS AND THE COMMENCEMENT OF THE SECOND WORLD WAR, 1918-1945 - MICHAEL, EDIAGBONYA (Innovare Journal of Social Sciences, 2021)
This paper discusses the power politics in the League of Nations. It examines the League of Nations as a formal international organisation whose purpose was the maintenance of world peace. It analyse the gross oppression of the major European powers over the smaller nations, as well as engaging in bitter rivalry yet the League of Nations could not take decisive actions. The inability of the League of Nations to prevent the occurrence of the Second World War also came to focus. Data for the study was obtained through oral interview as primary sources and secondary sources such as books, newspapers, articles, theses, dissertation journals etc. It was found that the establishment of the League of Nations became an acceptable concept because of casualties and devastation associated with the First World War. It was demonstrated that the League of Nations later became a toothless bull dog because it could not prevent the constant violations of its covenant by the major European powers. It was also found that the second world could have been avoided if the organisation was proactive in handling the issues that led to the war. It concluded that the League of Nations lacked the cohesive force to adequately intervene in conflict and crises.